Digital Comic Based on the Salib Kasih Tarutung Ecosystem as a Local Wisdom Learning Media - Rizka Nurani Hutasoit; Binari Manurung (Universitas Pendidikan Ganesha, 2025)
This study is motivated by ecosystem learning at the senior high school level, which still relies on conventional media, lacks interactivity, and has not optimally utilized the surrounding environmental potential. As a result, students have limited understanding of ecosystem components due to the lack of contextual learning media and minimal outdoor learning activities. Digital comics based on local wisdom are considered an alternative learning medium that is more engaging and relevant. This study aims to examine the feasibility, practicality, and effectiveness of ecosystem-based digital comics. The study employs the Thiagarajan development model and involves subject matter experts, media design experts, biology teachers, and students. The validation results indicate that the digital comics are considered feasible by experts. The practicality level falls into the very practical category based on teachers’ assessments and student trial results. The effectiveness test shows that the use of digital comics is able to improve students’ learning outcomes at a moderate level. It can be concluded that digital comics based on local wisdom are feasible, practical, and effective for use in biology learning. The findings imply that this media can be utilized by teachers to support contextual biology learning while fostering students’ learning motivation and environmental awareness.